Islamic Worldview: Konsep Jiwa Menurut Imam Ghazali - Mujahid, Kasori; Al Fani, Farid (Lembaga Yasin AlSys, 2025)
Imam Al-Ghazali, a great figure in the history of Islamic thought, made important contributions to understanding the concept of the soul. In his works, especially Ihya' Ulum al-Din, Ghazali describes the soul as an entity that is not only physical, but also has deep moral and spiritual dimensions. This research aims to examine the concept of the soul according to Imam Ghazali, with a focus on the division of the soul into three parts: rational soul, natural soul, and physical soul, as well as the relevance of Ghazali's teachings in modern life. The method used in this research is library research with a qualitative approach. The research results show that the rational soul plays a role as a controller that directs the physical and physical souls, and the importance of tazkiyah al-nafs or purification of the soul to achieve inner happiness and closeness to God. Ghazali's thinking remains relevant in an increasingly materialistic modern world, providing guidance for achieving balance between rational, emotional and spiritual dimensions. Thus, the concept of the soul according to Ghazali not only provides theological understanding, but also becomes a moral and ethical guide in everyday life.